The complete chloroplast genome sequence of Hydrangea luteovenosa (Hydrangeaceae). Issue 2 (12th December 2017) - Jeong, Keum Seon; Kim, Jung Sung; Kim, Hyuk-Jin; Oh, Seung Hwan; Choi, Kyung
Abstract: Hydrangea luteovenosa is a member of the family Hydrangeaceae. The complete chloroplast genome sequence of H. luteovenosa was characterized from MiSeq (Illumina Co.) pair-end sequencing data. The chloroplast genome of H. luteovenosa was 157, 494 bp in length with a pair of inverted repeats (IRs) (25, 126 bp) which were separated by a large single-copy (LSC) (86, 596 bp) and a small single-copy regions (SSC) (18, 646 bp). It contained 129 genes including 85 protein-coding genes, 36 tRNA genes, and 8 ribosomal RNA genes. The maximum-likelihood phylogenetic analysis with the previously reported chloroplast genomes showed that H. luteovenosa is most closely related to the tribe Hydrangeeae .